THE IMPACT OF SELF-DIRECTED LEARNING ON STUDENTS' THINKING ABILITIES: A LITERATURE ANALYSIS - Artikovna, Vafaeva Dilafruz (Journal of Learning on History and Social Sciences, 2024)
The article analyzes the importance of pedagogical interactive methods in organizing independent work of students in the higher education system. Attention is paid to the analysis of literature on increasing the effectiveness of lectures and practical classes using interactive methods